Thermally Oxidized Cooking Palm Oil-Induced Histopathological Alterations in Brain, Heart, Liver, and Kidney: A Systematic Review of Lipid Peroxidation and Inflammatory Mechanisms - Nimas Ayu Nirwanti; Ahmad Aulia Jusuf (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Repeated heating of cooking palm oils at high temperatures generates various toxic compounds, including lipid peroxidation products. These compounds are implicated in various diseases through oxidative stress and inflammation. This systematic review aims to evaluate the histopathological effects of thermally oxidized cooking oil (TOCO) consumption on the brain, heart, liver, and kidney, focusing on the roles of lipid peroxidation and inflammation. Methods: A systematic search was conducted in PubMed, Scopus, and Web of Science databases using predefined keywords and inclusion/exclusion criteria. Studies published between 2013 and 2024 investigating the histopathological effects of TOCO on the specified organs were included. Data on histopathological changes, markers of lipid peroxidation (malondialdehyde [MDA], 4-hydroxynonenal [4-HNE]), and inflammatory markers (TNF-α, IL-1β, IL-6) were extracted. Results: Seven studies met the inclusion criteria. The data revealed consistent histopathological changes across all four organs. In the brain, neuronal degeneration, astrogliosis, and microglial activation were observed. The heart exhibited cardiomyocyte hypertrophy, fibrosis, and inflammatory cell infiltration. The liver showed hepatocyte necrosis, steatosis, and inflammation. The kidneys presented with tubular necrosis, glomerular damage, and interstitial fibrosis. Elevated levels of MDA and 4-HNE were consistently reported in all affected tissues, along with increased expression of TNF-α, IL-1β, and IL-6. Conclusion: Consumption of TOCO induces significant histopathological damage in the brain, heart, liver, and kidney. The observed damage is strongly associated with increased lipid peroxidation and inflammatory responses. These findings highlight the potential health risks associated with consuming repeatedly heated cooking oils and underscore the need for public health awareness and strategies to mitigate these risks.